Intended Statistics Curriculum at the Elementary Level: Thailand vs. Indonesia - Dhanachat Anuniwat; Yoga Dwi Windy Kusuma Ningtyas (Pendidikan Matematika STKIP Kusuma Negara, 2024)
Mathematics occupies a central role in school education, with the mathematics curriculum serving as a critical tool for guiding curriculum reform. To identify the need for reform in specific contexts, it is necessary to examine curricula from a comparative perspective. Such an approach can yield valuable insights into the directions and priorities for curriculum reform. Accordingly, this study examined the current status of the intended statistics curriculum in Thailand and Indonesia. A qualitative content analysis was employed as the research design, with one mathematics curriculum document from Thailand and one from Indonesia purposively selected for analysis. The findings reveal that, in the domain of statistics, Indonesia introduces probability alongside statistics at the elementary level, whereas Thailand does not include probability at this stage. Furthermore, both countries place limited emphasis on incorporating a comprehensive statistical problem solving process within their curricula. It is important to note that this study focuses exclusively on the intended curriculum; further research is required to provide a more nuanced understanding.